Pemasaran Hijau Dan Keputusan Pembelian Konsumen Studi Pada Iklan Teh Kotak Dan Teh Botol - Edi Setiawan (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2015)
This study aimed to analyze the effect of ads with environmental messages and advertisement without an environmental message to the consumer buying decisions. The data used in this research is primary data obtained from the questionnaire. The total sample of 50 respondents using sampling method. Analysis technique is a method of Chi Square analysis, and hypothesis testing using descriptive analysis to determine range.The results showed that the variables ads with environmental messages and no significant positive effect on consumer buying decisions. Variable ads without environmental message and no significant positive effect on consumer buying decisions. And variables that have a dominant influence on consumer buying decisions are advertising with an environmental message.